Effects of integrated HRM on the optimization of marketing performance in tourism industry SMEs - Adya Hermawati; Abimanyu Tuwuh Sembhodo; Djawoto Djawoto (Jurnal Inovasi Ekonomi, 2022)
The purpose of this study is to analyze the effect of integrated human resource management on the optimization of marketing performance. The subject under study is the Tourism Industry SMEs. Hypothesis testing is done by multiple regression testing with data processing using SPSS software version 25. There are five hypotheses used in this study, with the results obtained are 1) individual performance has a significant effect on marketing performance, 2) innovation culture has a significant effect on marketing performance, 3) rewards have a significant effect on marketing performance, 4) individual performance, innovation culture, and rewards have a simultaneous effect on marketing performance.